Cloud Prediction of Network Security Situation - Shu Zhu; Lixia Liu; Lixia Liu (Dianxin kexue)
The existing algorithms of network security situation prediction were affected with subjective factors. The results of algorithms were highly relevant to selection data. An improved algorithm was proposed based on the algorithm of network security situation prediction based on cloud. It not only have the advantage of original algorithm that don't need to process the initial data in advance, but also solve the problem that errors caused by the results of the original algorithm isolate from the actual situation. Experiment results show that the algorithm is feasibility and effectiveness. The improved algorithm of network security situation prediction based on cloud can improve the accuracy of the results of network security situation prediction.